Observation of a resonance in the photodetachment of positronium negative ions. (July 2015) - Michishio, Koji; Kuma, Susumu; Kanai, Tsuneto; Azuma, Toshiyuki; Wada, Ken; Mochizuki, Izumi; Hyodo, Toshio; Yagishita, Akira; Nagashima, Yasuyuki
Synopsis: The positronium negative ion, e − e + e −, is one of the simplest three body bound-states. As its constituents have a unique mass ratio, the ion is an attractive candidate for the investigation of the genuine three-body problem. In the present work, laser spectroscopy of this ion has been demonstrated in the UV region. A shape resonance near the positronium ( n =2) formation threshold was clearly observed and the resonance energy was estimated.